A ALFABETIZAÇÃO E OS DESAFIOS PARA O PROFESSOR RECÉM-FORMADO - FERREIRA, ZENI DE OLIVEIRA MUNIZ (2017)
Historically, in our educational context, the performance of teachers, especially for the newly graduated, faces several challenges, especially when it comes to literacy in the initial grades of Elementary School. The teacher who starts his or her literacy career usually faces large classrooms and needs to deal with students who have different knowledge and experience, and some students often have difficulties in acquiring reading and writing and need interventions adjusted to their real needs. The present research proposes an investigation into the challenges faced by newly trained literacy teachers, based on the following problem: what challenges does a newly trained teacher face in a literacy room, in interaction with the knowledge and practices of their literacy practice? We have developed a literature review on teacher education, Pedagogy, Literacy/Literacy and Training Policies for literacy students, with the following theoretical main references: Tardif (2014); Nóvoa, 2009; Gatti and Barreto (2009); Saviani (2005; 2008); Libâneo (2006; 2010; 2012); Pimenta (2012); Franco (2003; 2005; 2012); Bahia (2016); Gatti (2010; 2013; 2014); Gatti, Barreto and André (2011); Monteiro (2014); Mortatti (2000, 2006); Albuquerque (2007); Ferreiro and Teberosky (1985) and Teberosky (1997). We conducted a field research, with the participation of five literacy teachers from the public school of Santo André. The instruments for the data collection and analysis were composed of a questionnaire to delineate the profile of the subjects and conduct deepening interviews. The data analysis of the interviews is based on the Content Analysis Methodology, proposed by Franco (2003). The analyzed categories considered self-presentation and career choice; initial and continuing training/knowledge; literacy-theories and practices; the internship as a pedagogical practice, as well as the attributions that mark and define the constitution of the newly formed teacher-literate identity. Regarding the challenges, we observe as results: weak initial training that distances the theory of practice; classrooms crowded with students; gaps in supervision; curriculum with more emphasis on theories than on literacy practices/ methodologies; lack of planning or even of a political pedagogical project that guides the newly trained teacher-literate in his/her work; besides the discontinuation of the policies of continuous formation.